2014
DOI: 10.1016/j.drugalcdep.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes and their relationship to maternal buprenorphine dose during pregnancy

Abstract: Background Buprenorphine pharmacotherapy for opioid-dependent pregnant women is associated with maternal and neonatal outcomes superior to untreated opioid dependence. However, the literature is inconsistent regarding the possible existence of a dose-response relationship between maternal buprenorphine dose and neonatal clinical outcomes. Methods The present secondary analysis study (1) examined the relationship between maternal buprenorphine dose at delivery and neonatal abstinence syndrome (NAS) peak score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 14 publications
2
51
0
Order By: Relevance
“…Similar to previous smaller studies, we found that dose of maintenance opioids did not modify the risk of NAS. 8,9 Furthermore, our findings provide important information that builds on previous studies of OPR use in pregnancy 3,35,36 and several publications describing tobacco and SSRI use in the context of opioid maintenance. [10][11][12] Both tobacco and SSRIs have been described in the literature as having individual withdrawal syndromes and unique toxidromes.…”
Section: Figurementioning
confidence: 74%
“…Similar to previous smaller studies, we found that dose of maintenance opioids did not modify the risk of NAS. 8,9 Furthermore, our findings provide important information that builds on previous studies of OPR use in pregnancy 3,35,36 and several publications describing tobacco and SSRI use in the context of opioid maintenance. [10][11][12] Both tobacco and SSRIs have been described in the literature as having individual withdrawal syndromes and unique toxidromes.…”
Section: Figurementioning
confidence: 74%
“…50 No relationship has been found between maternal opioid dose and NAS. 51 Neither methadone nor buprenorphine were approved for use in pregnancy.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…The relationship between maternal dose of buprenorphine at the time of delivery and the severity of NAS has been inconsistent, as some authors have found no relationship [6], while others have found that infants with a NAS score of zero were more likely to have been exposed to a lower dose of buprenorphine during pregnancy [7] . A small study of 10 infants born to women maintained on buprenorphine during pregnancy found that total buprenorphine meconium concentrations were correlated with NAS scores >4 [8] .…”
Section: Introductionmentioning
confidence: 95%